"They loved gambling more than me." Women's experiences of gambling‐related harm as an affected other. Issue 2 (11th May 2022) - McCarthy, Simone; Thomas, Samantha L.; Pitt, Hannah; Warner, Elyse; Roderique‐Davies, Gareth; Rintoul, Angela; John, Bev
Abstract: Background: Gambling poses a global threat to public health due to its far‐reaching impacts. Research has demonstrated a ripple effect of harmful gambling on social network members and broader communities. While researchers have documented extreme harms associated with an affected other, limited research has qualitatively investigated how women describe their concerns about the gambling of a social network member, and any subsequent negative impacts on their own lives. Methods: An online panel survey was conducted with women aged 18 years and older, who gambled at least once in the last 12 months, and resided in the Australian states of Victoria and New South Wales. This paper focused on the open text responses of a subsection of the sample ( n  = 136) who reported being negatively impacted by someone else's gambling. The study utilised reflexive thematic analysis to interpret the data. Results: Results indicated that women were concerned about the gambling behaviours of a broad range of social network members. Open text responses regarding the nature of these concerns mostly related to individualised paradigms of gambling behaviour – including whether the participant perceived their network member could afford to gamble, was being responsible with their gambling, or were gambling too frequently. Participants experienced a range of negative impacts including significant financial issues, relationship difficulties, poorer emotional wellbeing as a result of worrying about the gambler, and loss of trust. Some described the negative experiences associated with growing up with a parent who gambled. Conclusion: The research demonstrates the broad impacts of gambling on affected others. This study enhances our understanding of how women are harmed by gambling and considers the complexities of their experiences and relationships with the gambler. This extends knowledge beyond quantitative descriptors of harm among affected others and provides a critical reflection on the nuances of women's experiences with gambling and gambling harm.